The Influence of Social Media Influencers on Purchase Intentions for Halal Cosmetic Products in Batam - Fasha, Andina; Indriyani, Monika Putri; Nurjanah, Listia (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study aims to examine how social media influencers affect the purchase intentions of Muslim consumers in Batam City toward halal cosmetic products, emphasizing their mediating role in product quality, brand equity, credibility, and information usefulness. Methodology/approach: A quantitative survey method was used. Data were gathered through an online questionnaire from 308 Muslim women in Batam who had been exposed to halal cosmetic content by beauty influencers. Purposive sampling was applied, and Smart PLS 4 was used for data analysis. Results/findings: Product quality, brand equity, information credibility, and information usefulness positively influence perceptions of social media influencers. These influencers significantly affect purchase intentions and mediate the relationship between the four antecedent factors and consumers’ intentions to buy. Conclusions: Social media influencers play a crucial mediating role in shaping Muslim consumers' purchase intentions for halal cosmetics. Strategic collaboration with credible influencers and the promotion of relevant, Sharia-compliant content are essential for effective digital marketing in the halal cosmetic industry. Limitations: The study focuses only on Muslim women in Batam and uses online surveys, excluding emotional or subjective factors. Other variables like price, packaging, and availability were not analyzed. Contribution: This study extends the Theory of Planned Behavior in digital marketing and offers practical guidance for halal cosmetic businesses in designing influencer-based strategies.